Common good dynamics in Copanatoyac: development process indicators in a rural, indigenous municipality of Mexico - Nebel, Mathias (Journal of global ethics, 2025)
The aim of the article is to understand how common good dynamics shape the rural, mainly indigenous municipality of Copanatoyac in Guerrero, Mexico. Based on the data collected in 2022 by the ipbc (Instituto Promotor del Bien Común) research team, we use the common good approach to development to offer a narrative of the municipality’s trends on governance, justice, stability, collective agency, and humanity. After a brief introduction on how a common good approach can help interpret key social processes and development trends, the first part concentrates on what the data shows about the five main triggers of common good dynamics. The second part investigates how Basic Common Goods (bcg) are created, distributed, and governed in the municipality. Our main results are (a) that the modern state and its institutions are not only failing to promote local common good dynamics but are in fact a hindrance to the common good; and (b) that while collective agency to address and solve common problems is high, it reaches its limit in two key domains: the ability to earn enough to live well, and systemic humiliation and injustice.